Applying a cluster-analysis approach to monitor training load in male volleyball during the preseason period - Kerpe, G.; Zuoza, A. K.; Conte, D. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study aimed to (1) classify the external-load measures carried out during the preseason period by male volleyball players via cluster technique identifying the most important external-load measures and (2) assess the differences between clusters in internal-load variables.